Effect of early and progressive exercises on post-caesarean section recovery among women attending women’s heath hospital - Youness, Entisar; Ibrahim, Walaa (International Journal of Advanced Nursing Studies, 2017)
Background: Cesarean section is the oldest surgery performed in obstetrics. Time needed for recovery of post cesarean section woman is more than those needed for vaginal delivery. The nursing role is to make women after C. S more independent in resuming their daily activities as soon as possible. This can be achieved by early exercises to faster her recovery and reduce complications associated with prolonged bed rest after C.S.The study aimed to assess the effect of early and progressive exercises on C. S recovery among post caesarean women for women attending Women’s Health Hospital, Assiut University, Egypt.Methods: A study and control quasi-experimental design used on 340 posts cesarean section women divided into two groups, study and control, each group contained 170 postpartum women. A structured interviewing questionnaire used as a tool which included Sociodemographic, Obstetric characteristics and follow-up data.Results: Findings of this study revealed that there were significant differences between both groups regarding post-cesarean section recovery variables, which included analgesics required, self-void after catheter removal, breast feeding, oral hydration, and first flatus passed after exercises as per the independent t-test (p<0.05).Conclusion: Early and progressive exercises had an effective role in improving post cesarean section women recovery.Recommendations: Early and progressive exercises should be encouraged as a routine part of care for women within 2 hours after cesarean section.